The Effect of Aeration on Aerobic Biofilter Using Polyethylene Terephthalate Media for Chicken Slaughterhouse Liquid Waste - Agus Surono; Suprapto; Ahmad Dwi Arga; Aigah Ameilia Manullang (Institut Teknologi Sepuluh Nopember, 2023)
Chicken Slaughterhouse is one of the industries that process live chickens into ready-to-eat chicken meat products. Many chicken slaughterhouses still need liquid waste treatment technology and directly discharge it into the aquatic environment. RPA liquid waste has a high organic content that will cause environmental pollution with unpleasant odors and decay. This study uses an aerobic wastewater treatment method by utilizing aerobic microorganisms in wastewater that are attached to biofilter media to form biofilms. This study aims to reduce the concentration of COD, BOD, TSS, and ammonia and change the pH value of RPA liquid waste with aerobic biofilter treatment using honeycomb media from Polyethylene Terephthalate and to get the best aeration flow rate to reduce the concentration of pollutants from the aerobic biofilter reactor. In this study, the residence time and the addition of air discharge in the aeration process are varied. The results of this study show that there has been a decrease in the concentration of COD, BOD, TSS, and ammonia and changes in pH values following PERMENLHK No 5 of 2014 concerning the quality standards of slaughterhouse wastewater with the best aeration flowrate recommendation is 15 liters/minute.